Protections of Natural Ressources Through a Sacred Prohibition: the rahui on Rapa iti - Ghasarian, Christian (Canberra: Anu Press; The Australian National University, 2016)
The management of natural resources implies conceptions of ownership and property that provide precious information on the way a society perceives itself. Established moralities on the matter are sometimes sustained by a sacredness that reinforces the values and principles at stake. In the case of ideological and environmental change, the sacred conceptions most of the time adjust to new circumstances and become part of the cultural dynamics. An invisible and superior force, associated with the past and the ancestors, legitimates the new social order.¹ Therefore, compliance with sacred models can ensure protection in the present life.